Tracking growth in the euro area subject to a dimensionality problem - Mariarosaria Comunale; Francesco Paolo Mongelli (European Central Bank (ECB), 2021)
We investigate which variables have supported growth in the euro area over the last 30 years. This is a challenging task due to dimensionality problems: a large set of potential determinants, limited data, and the prospect that some variables could be non-stationary. We assemble a set of 35 real, financial, monetary, and institutional variables for nine of the original euro area countries covering the period between 1990Q1 and 2016Q4. Using the Weighted-Average Least Squares method, we gather clues about which variables to select. We quantify the impact of various determinants of growth in the short and long runs. Our main finding is the positive and robust role of EU institutional integration on long-term growth for all countries in the sample. An improvement in competitiveness matters for growth in the overall euro area in the long run, as well as a decline in sovereign and systemic stress. Debt over GDP negatively influences growth for the periphery, but only in the short run. Property and equity prices have a significant impact only in the short run, whereas the loans to non-financial corporations positively affect the core euro area. An increase in global GDP also supports growth in the euro area.
Keywords: C23; E40; F33; F43; 330; euro area; GDP growth; monetary policy; fiscal policy; institutional integration; institutional reforms; systemic stress